Financial inclusion dynamics in WAEMU: Was digital technology the missing piece? - Melain Modeste Senou; Wautabouna Ouattara; Denis Acclassato Houensou (Cogent Economics & Finance, 2019)
Like most of International Institutions, the Central Bank of West African States (BCEAO) considers universal access to finance as key to empowering disadvantaged people. Fitting into that context, this study aims to assess the accelerating role of digital technologies using mobile phone penetration and internet usage as broad indicators, on the dynamics of financial inclusion in WAEMU. Using data from the Central Bank of West African States (BCEAO) and the International Telecommunication Union (ITU) over the periods 2006-2017, we estimated first a random effect model and thereafter a system GMM devised by Arrelano-Bover/Bundell-Bond, to correct the endogeneity issue raised from the static model. Findings show that beyond the specific effects of mobile phone penetration and Internet usage, the joint use of these two technologies is very key to financial inclusion in the WAEMU countries. It urges then for policy makers to take steps toward the availability, accessibility, affordability and to design flexible legislation pertaining to mobile financial services providers in order to accelerate financial inclusion in that region.
Keywords: C01; G29; O10; O30; 330; Financial inclusion; digital technology; GMM; WAEMU